2014
DOI: 10.1371/journal.pone.0095693
|View full text |Cite|
|
Sign up to set email alerts
|

The Exploration-Exploitation Dilemma: A Multidisciplinary Framework

Abstract: The trade-off between the need to obtain new knowledge and the need to use that knowledge to improve performance is one of the most basic trade-offs in nature, and optimal performance usually requires some balance between exploratory and exploitative behaviors. Researchers in many disciplines have been searching for the optimal solution to this dilemma. Here we present a novel model in which the exploration strategy itself is dynamic and varies with time in order to optimize a definite goal, such as the acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(148 citation statements)
references
References 49 publications
2
144
1
1
Order By: Relevance
“…We hypothesize that the temporal inter-class intervals (ICIs) distribution will converge for stationary versus non-stationary behaviors. The empirical cumulative distribution function (eCDF) for time between the same actions demonstrates that the difference between non-stationary and stationary ICIs distributions diminished during late exploration (Fig.7), consistent with the idea that exploration-exploitation trade-off depends on experience in the environment (16). More surprisingly, we observed that the our extracted stereotypical grooming sequence appear to be affected by experience as well.…”
Section: Exploration Versus Exploitationsupporting
confidence: 84%
“…We hypothesize that the temporal inter-class intervals (ICIs) distribution will converge for stationary versus non-stationary behaviors. The empirical cumulative distribution function (eCDF) for time between the same actions demonstrates that the difference between non-stationary and stationary ICIs distributions diminished during late exploration (Fig.7), consistent with the idea that exploration-exploitation trade-off depends on experience in the environment (16). More surprisingly, we observed that the our extracted stereotypical grooming sequence appear to be affected by experience as well.…”
Section: Exploration Versus Exploitationsupporting
confidence: 84%
“…captive or wild origin), which will govern decisions about dispersing from the release site and control the rate of learning and adapting to differences between the source and release environments (Stamps & Swaisgood, ; Le Gouar et al , ). However, it is highly likely that these initial behavioral responses will not be optimal in the new environment, and should therefore change as the animal gains experience in its new habitat, becoming more adaptive with time (Berger‐Tal et al , ). This change can be termed ‘post release behavioral modification’, and knowledge of this behavioral change can assist wildlife managers in evaluating the state of the translocated animals (Berger‐Tal & Saltz, ).…”
Section: Introductionmentioning
confidence: 99%
“…These reserves are entirely fenced, leading to intense competition for resources and territories (Ferreira & Hofmeyr, 2014). Introduced animals also face the additional challenge of being in an unfamiliar environment where they need to explore and learn the locations of resources (Berger-Tal et al, 2014). The fitness and survival of introduced large carnivores are therefore directly affected by their spatial responses to competitors and resource distribution.…”
Section: Introductionmentioning
confidence: 99%